Recent advances in the understanding of how neuropeptide Y and α-melanocyte stimulating hormone function in adipose physiology. (1st October 2016) - Shipp, Steven L.; Cline, Mark A.; Gilbert, Elizabeth R.
ABSTRACT: Communication between the brain and the adipose tissue has been the focus of many studies in recent years, with the "brain-fat axis" identified as a system that orchestrates the assimilation and usage of energy to maintain body mass and adequate fat stores. It is now well-known that appetite-regulating peptides that were studied as neurotransmitters in the central nervous system can act both on the hypothalamus to regulate feeding behavior and also on the adipose tissue to modulate the storage of energy. Energy balance is thus partly controlled by factors that can alter both energy intake and storage/expenditure. Two such factors involved in these processes are neuropeptide Y (NPY) and α-melanocyte stimulating hormone (α-MSH). NPY, an orexigenic factor, is associated with promoting adipogenesis in both mammals and chickens, while α-MSH, an anorexigenic factor, stimulates lipolysis in rodents. There is also evidence of interaction between the 2 peptides. This review aims to summarize recent advances in the study of NPY and α-MSH regarding their role in adipose tissue physiology, with an emphasis on the cellular and molecular mechanisms. A greater understanding of the brain-fat axis and regulation of adiposity by bioactive peptides may provide insights on strategies to prevent or treat obesity and also enhance nutrient utilization efficiency in agriculturally-important species.